Transcendental Spirituality and Acquaintance With the Activities of the Domestic National Transplant Center as Factors Shaping Attitudes Toward Organ Donation. (June 2017) - Melnikov, Semyon; Ashkenazi, Tamar; Amara, Muhammad; Peles Bortz, Anat
Context: Organ donation has been shown to be perceived as inappropriate by religiously observant individuals. The impact of spirituality level on attitudes toward organ donation has not been broadly explored. Objective: To explore the contribution of ethnicity, spirituality, level of religious observance, and acquaintance with the activities of the Israel National Transplant Center (INTC) to forming attitudes toward organ donation among Jews and Muslim Arabs in Israel. Design: A descriptive cross-sectional survey. Participants: Three hundred five (65.2%) Jewish and 163 (34.8%) Muslim Arab respondents living in Israel. Results: Jewish respondents had more positive attitudes toward organ donation than Muslim Arabs. Muslim Arabs had a higher mean spirituality score than Jews. Gender, age, ethnicity, level of religious observance, education, 4 spirituality dimensions, and acquaintance with the activities of the INTC explained 41.5% of the variance in attitudes to organ donation. Transcendental spirituality, acquaintance with the activities of the INTC, and level of religious observance had the highest contribution to explaining attitudes to organ donation, while gender and age had a low contribution. Ethnicity, education, and the 3 other spirituality dimensions were not found to have a significant contribution. Conclusion: A multifaceted approach to improving attitudes toward organ donation among Jews and Muslim Arabs in Israel is important.